2020
DOI: 10.1177/0018726720945775
|View full text |Cite
|
Sign up to set email alerts
|

It’s not just what you say, it’s how you say it: How callings influence constructive voice delivery

Abstract: How employees communicate their ideas at work shapes how their ideas are received. When employees constructively communicate their ideas, the value of those ideas can be more readily recognized. Conversely, ideas that are not communicated constructively may be overlooked, ignored, or rejected, regardless of their potential value to an organization. This research contributes to the employee voice literature by introducing the concept of constructive voice delivery and examining its relationship with callings. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 76 publications
1
22
0
Order By: Relevance
“…In line with this presumption, we propose that employees who feel a calling attaches great importance to the meaning gained from work rather than focusing on the material benefits (Chang et al, 2021;Hirschi, 2012), which motivates them to continuously take charge as an effective way to realize work meaning (Bailey et al, 2019;Lysova et al, 2019). In addition, calling-oriented employees generally report higher commitment and obligation to the organization (Neubert and Halbesleben, 2015;Rawat and Nadavulakere, 2015;Romney, 2021), impelling them to fulfill their obligation through taking charge based on normative beliefs (Chen et al, 2022;Eisenberger et al, 2001).…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…In line with this presumption, we propose that employees who feel a calling attaches great importance to the meaning gained from work rather than focusing on the material benefits (Chang et al, 2021;Hirschi, 2012), which motivates them to continuously take charge as an effective way to realize work meaning (Bailey et al, 2019;Lysova et al, 2019). In addition, calling-oriented employees generally report higher commitment and obligation to the organization (Neubert and Halbesleben, 2015;Rawat and Nadavulakere, 2015;Romney, 2021), impelling them to fulfill their obligation through taking charge based on normative beliefs (Chen et al, 2022;Eisenberger et al, 2001).…”
Section: Introductionmentioning
confidence: 78%
“…employee proactivity; Cai et al, 2022). Although previous research has demonstrated the effectiveness of calling in advancing voice (Chen et al, 2022;Romney, 2021) and OCB (Xie et al, 2017), knowledge about whether career calling promotes taking charge remains scarce. Career calling is an internal psychological construct with three salient features, including goal orientation, meaning and purpose pursuit, and prosocial intention (Duffy et al, 2018).…”
Section: Career Calling and Taking Chargementioning
confidence: 99%
See 2 more Smart Citations
“…The correlation was found to be positive and significant (r = .24). In a hospital setting, Romney (2020;Study 3) showed that the positive relation between employees' calling and manager's ratings of their performance (r = .24) was suppressed by the managers' perception of how effective employees deliver their voices regarding suggestions or comments on how work might be conducted more effectively (constructive voice delivery).…”
Section: Empirical Evidence Supporting the Relation Between Calling A...mentioning
confidence: 99%